RADAR SIMULATION USING GPU-BASED TEXTURE MAPPING - Nguyễn Trung Kiên; Trương Khánh Nghĩa; Nguyễn Thị Lan (Tạp chí Khoa học Đại học Đà Lạt, 2017)
Radar is widely used and integrated in many different kinds of weapons and equipment. During the design and development of a radar-based training system, the simulated operation of radar screen is really important. However, this work is complicated with heavy computation. Thus, this paper proposed a GPU-based method to simulate the contents and effects of a working radar screen. Most of the computation is performed in GPU so that the radar simulation can be run in real time and it can be integrated in a larger simulation system.